Patient and Clinician Perspectives of Physical Therapy for Walking Difficulties in Multiple Sclerosis - Plummer, Prudence; Stewart, Andrea; Anderson, Jessica N. (Multiple sclerosis international, 2023)
Gait speed is frequently the primary efficacy endpoint in clinical trials of interventions targeting mobility in people with multiple sclerosis (MS). However, it is unclear whether increased gait speed is a meaningful outcome for people living with MS. The purpose of this study was to identify the most important aspects of mobility for people with MS and physical therapists and to explore how patients and clinicians perceive whether physical therapy has been effective. Forty-six people with MS and 23 physical therapy clinicians participated in a focus group, one-on-one interview, or electronic survey. The focus group and interview data were transcribed and coded to identify themes. Free-text survey responses were also coded, and multiple-choice options were analyzed for frequency. Among people with MS, falls and difficulties getting out into the community were identified as highly important mobility limitations. Clinicians also identified falls and safety as a priority. Walking speed was infrequently described as a problem, and although gait speed is often measured by clinicians, improving gait speed is rarely a treatment goal. Despite their emphasis on safety, clinicians lacked certainty about how to objectively measure improvements in safety. People with MS evaluated physical therapy effectiveness based on the ease by which they can do things and acknowledged that “not getting worse” is a positive outcome. Clinicians evaluated effectiveness based on the amount of change in objective outcome measures and by patient and caregiver reports of improved function. These findings indicate that gait speed is not of major importance to people with MS or physical therapy clinicians. People with MS want to be able to walk further and without an assistive device, and they want to avoid falls. Clinicians want to maximize safety while improving functional ability. Clinicians and patients may differ in their expected outcomes from physical therapy.